Government Subsidies : Concepts, International Trends, and Reform Options - Schwartz, Gerd (IMF Working Papers; Working Paper ;, 1995)
This paper addresses the problems of defining and measuring government subsidies, examines why and how government subsidies are used as a fiscal policy tool, assesses their economic effects, appraises international empirical evidence on government subsidies, and offers options for their reform. Recent international trends in government subsidy expenditure are analyzed for the 16-year period from 1975 to 1990, using general government subsidy data for 60 countries from the System of National Accounts (SNA) and central government expenditure on subsidies and other current transfers for 68 countries from Government Finance Statistics (GFS). The paper reviews major policy options for subsidy reform, focusing on ways to improve the cost-effectiveness of subsidy programs.